Application of silver-bismuth tungstate catalyst in preparation of methanol from light-driven CO2
By loading silver particles onto a bismuth tungstate catalyst, the LSPR effect is utilized to enhance light absorption and photothermal conversion, solving the problems of high energy consumption and insufficient catalyst stability in existing photothermal catalysis technologies, and achieving efficient CO2 conversion to methanol.
Patent Information
- Application Number
- CN202511112589.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-09
- Publication Date
- 2025-11-21
AI Technical Summary
Existing photothermal catalysis technology has limitations in CO2 resource utilization, including high energy consumption, limited light absorption range, easy recombination of photogenerated electron-hole pairs, and insufficient catalyst stability, which restrict its practical application.
A silver-bismuth tungstate catalyst is used. By loading 0.1-0.7% silver particles with a size of 20-50 nm onto bismuth tungstate, the localized plasmon resonance (LSPR) effect of silver is utilized to enhance the light absorption performance and generate high-energy hot electrons under light irradiation to achieve photothermal conversion without external heating, thus promoting the conversion of CO2 into methanol.
It improved photocatalytic efficiency, reduced reaction activation energy, enhanced CO2 adsorption and methanol yield, and improved catalyst stability and utilization of photogenerated electrons.
Smart Images

Figure CN120987727A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of technology, and more particularly to the application of a silver-bismuth tungstate catalyst in the photo-driven production of methanol from CO2. Background Technology
[0002] With the intensification of the global greenhouse effect, the utilization of CO2 resources has become a research hotspot. Among them, photothermal catalysis technology is considered an important pathway to achieve efficient CO2 conversion because it can synergistically utilize light and heat energy to activate inert CO2 molecules. Photothermal catalysis coupling can achieve efficient catalytic reduction of CO2 under mild conditions. Existing technologies, such as patent CN118146069A, propose a bismuth tungstate nanosheet catalyst containing oxygen vacancies, which catalyzes the reduction of CO2 to methanol under the synergistic effect of ultraviolet-visible light irradiation and external heating (60-120℃). This technology significantly improves the methanol yield by enhancing CO2 adsorption and inhibiting carrier recombination through oxygen vacancies. However, this method depends on an external heat source, requires an additional high-temperature environment, and has high energy consumption, limiting its practical application. Furthermore, most photothermal catalysis catalysts can only utilize the short-wavelength region of ultraviolet or visible light, with a limited light absorption range. The generated photogenerated electron-hole pairs are prone to recombination, resulting in low quantum efficiency. In addition, the catalysts lack stability and are easily deactivated under high temperature and light irradiation. Summary of the Invention
[0003] The purpose of this invention is to provide an application of a silver-bismuth tungstate catalyst in the photo-driven production of methanol from CO2. The silver-bismuth tungstate catalyst has a silver loading of 0.1-0.7% on the bismuth tungstate catalyst, and the size of the silver particles is 20-50 nm. The catalyst has a large specific surface area, strong photoresponse ability, enhanced photothermal effect, large CO2 adsorption capacity, and high methanol yield.
[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0005] This invention provides an application of a silver-bismuth tungstate catalyst in light-driven methanol production, the method of which includes the following steps:
[0006] A silver-bismuth tungstate catalyst was dispersed in water, and CO2 gas was introduced under closed conditions to carry out a catalytic reaction under light irradiation to obtain methanol.
[0007] The initial temperature of the catalytic reaction is 25–30°C;
[0008] The size of the silver particles in the silver-bismuth tungstate catalyst is 20–50 nm.
[0009] The silver loading in the silver-bismuth tungstate catalyst is 0.1% to 0.7% of the mass of bismuth tungstate;
[0010] The preparation method of the silver-bismuth tungstate catalyst includes the following steps:
[0011] Bismuth tungstate nanosheets, silver salt, and water were mixed, and the pH was adjusted to 10-12. The resulting mixed solution was then mixed with a reducing agent to carry out a reduction reaction, thus obtaining a silver-bismuth tungstate catalyst.
[0012] Preferably, the method for preparing the bismuth tungstate nanosheets includes the following steps:
[0013] Sodium tungstate dihydrate, hexadecyltrimethylammonium bromide, bismuth nitrate pentahydrate, and water were mixed and subjected to a hydrothermal reaction to obtain bismuth tungstate nanosheets.
[0014] Preferably, the molar ratio of sodium tungstate dihydrate to hexadecyltrimethylammonium bromide is 1 mmol:0.25 g to 1 mmol:1 g, and the molar ratio of sodium tungstate dihydrate to bismuth nitrate pentahydrate is 1:1.8 to 1:2.4.
[0015] Preferably, the hydrothermal reaction is carried out at a temperature of 100–180°C for a duration of 12–48 hours.
[0016] Preferably, the silver salt includes silver nitrate, silver acetate, silver sulfate, or silver chloride; the mass ratio of the silver salt to bismuth tungstate is 1:500 to 1:7000.
[0017] Preferably, the alkaline solution used to adjust the pH value includes sodium hydroxide solution, sodium bicarbonate solution, or ammonia water, and the concentration of the alkaline solution is 1 to 3 mol / L.
[0018] Preferably, the reducing agent comprises ascorbic acid and sodium citrate dihydrate, wherein the molar ratio of ascorbic acid to sodium citrate dihydrate is 1:3 to 1:8, and the molar ratio of silver salt to reducing agent is 1:1 to 1:10.
[0019] Preferably, the reduction reaction is carried out at a temperature of 80–120°C for 1–5 hours.
[0020] Preferably, the pressure of the CO2 gas is 1 to 3 MPa.
[0021] Preferably, the light source for illumination includes a xenon lamp, a mercury lamp, or an LED lamp with a wavelength of 350–780 nm;
[0022] The catalytic reaction takes 1 to 6 hours.
[0023] The beneficial effects of this invention are:
[0024] This invention mixes bismuth tungstate nanosheets, silver salt, and water to obtain a silver-bismuth tungstate catalyst, which is then used in the photo-driven CO2 to methanol reaction. In this silver-bismuth tungstate catalyst, silver is supported on a catalyst carrier. The introduction of Ag not only significantly enhances the catalyst's light absorption performance and expands the light absorption range, but also allows silver to induce localized heating in the ultraviolet-visible region using strong localized plasmon resonance (LSPR), requiring no additional thermal energy input. Under illumination, the catalyst generates a large number of high-energy hot electrons. The energy of these hot electrons couples to phonon modes through electron-phonon interactions, raising the temperature of the metal lattice. This energy is then dissipated into the surrounding environment through lattice vibrations, thus achieving photothermal conversion and driving the reaction. This enhances the CO2 to methanol conversion without external heating. Compared to photocatalysis alone, this invention not only lowers the activation energy of the reaction but also significantly improves the efficiency of photocatalysis. Simultaneously, electrons can transfer from the semiconductor to the metal, reducing the recombination of photogenerated electron-hole pairs and promoting the transfer and utilization of photogenerated electrons.
[0025] In addition, by adjusting the pH value to control the Ag particle size, this invention further optimizes the LSPR effect of silver, thereby enhancing the absorption of sunlight and its conversion efficiency into heat energy, which helps to improve the overall catalytic performance, exhibits better photocatalytic CO2 reduction to methanol performance, and thus improves the CO2 adsorption capacity and methanol yield. Attached Figure Description
[0026] Figure 1 The XRD patterns of the silver-bismuth tungstate catalysts prepared under different pH conditions in Example 1 (bismuth tungstate), 0.1% Ag / BWO-11, and Example 2 are shown.
[0027] Figure 2 In the image, a is the SEM image of bismuth tungstate in Example 1, and b is the SEM image of 0.1% Ag / BWO-11 in Example 1.
[0028] Figure 3 The N2 adsorption-desorption isotherm distribution (a) and pore size distribution (b) are for bismuth tungstate prepared in Example 1, 0.1% Ag / BWO-11, and silver-bismuth tungstate catalyst prepared in Example 2 under different pH conditions.
[0029] Figure 4 The UV-Vis DRS spectra (a), Tauc curves (b), and temperature change curves under illumination (c) of the silver-bismuth tungstate catalysts prepared under different pH conditions in Example 1 (bismuth tungstate, 0.1% Ag / BWO-11) and Example 2 are shown.
[0030] Figure 5In the figures, a is a graph showing the performance of the silver-bismuth tungstate catalysts prepared in Example 1 with bismuth tungstate, 0.1% Ag / BWO-11, and Example 3 under different Ag dosage conditions for photo-driven CO2 to methanol production; b is a graph showing the performance of the silver-bismuth tungstate catalysts prepared in Example 1 with bismuth tungstate, 0.1% Ag / BWO-11, and Example 2 under different pH conditions for photo-driven CO2 to methanol production; c is a graph showing the performance of the silver-bismuth tungstate catalysts prepared in Example 1 with bismuth tungstate, 0.1% Ag / BWO-11, and existing catalysts for photothermal methanol production.
[0031] Figure 6 The CO2-TPD diagram of bismuth tungstate and 0.1% Ag / BWO-11 in Example 1 is shown.
[0032] Figure 7 In the table, a represents the performance evaluation of 0.1% Ag / BWO-11 under different reaction conditions within 4 hours in Example 1, and b represents the performance evaluation of 0.1% Ag / BWO-11 under different reaction conditions at 4 hours. Detailed Implementation
[0033] This invention provides an application of a silver-bismuth tungstate catalyst in photo-driven CO2 to methanol production, the method of which includes the following steps:
[0034] A silver-bismuth tungstate catalyst was dispersed in water, and CO2 gas was introduced under closed conditions to carry out a catalytic reaction under light irradiation to obtain methanol.
[0035] The initial temperature of the catalytic reaction is 25–30°C;
[0036] The size of the silver particles in the silver-bismuth tungstate catalyst is 20–50 nm.
[0037] The silver loading in the silver-bismuth tungstate catalyst is 0.1% to 0.7% of the mass of bismuth tungstate;
[0038] The preparation method of the silver-bismuth tungstate catalyst includes the following steps:
[0039] Bismuth tungstate nanosheets, silver salt, and water were mixed, and the pH was adjusted to 10-12. The resulting mixed solution was then mixed with a reducing agent to carry out a reduction reaction, thus obtaining a silver-bismuth tungstate catalyst.
[0040] In this invention, unless otherwise specified, all raw materials required for preparation are commercially available products well known to those skilled in the art.
[0041] In this invention, the silver loading in the silver-bismuth tungstate catalyst is preferably 0.1 to 0.7% of the mass of bismuth tungstate, and more preferably 0.3 to 0.5%.
[0042] In this invention, the preparation method of the silver-bismuth tungstate catalyst preferably includes the following steps:
[0043] Sodium tungstate dihydrate, hexadecyltrimethylammonium bromide, bismuth nitrate pentahydrate, and water were mixed and subjected to a hydrothermal reaction to obtain bismuth tungstate nanosheets.
[0044] The bismuth tungstate nanosheets, silver salt, and water were mixed, the pH value was adjusted, and the resulting mixed solution was mixed with a reducing agent to carry out a reduction reaction, thereby obtaining a silver-bismuth tungstate catalyst.
[0045] In this invention, sodium tungstate dihydrate and hexadecyltrimethylammonium bromide are added sequentially to water to obtain an aqueous solution of sodium tungstate. Then, bismuth nitrate pentahydrate is added to the aqueous solution of sodium tungstate under stirring, and the mixture is stirred for 1 hour. After stirring, the suspension is poured into a 100 mL hydrothermal synthesis vessel for hydrothermal reaction. The mixture is then naturally cooled to room temperature in an oven, washed with water multiple times, and dried to obtain bismuth tungstate nanosheets, denoted as BWO.
[0046] This invention does not have a specific limitation on the amount of water used, as long as sodium tungstate dihydrate and hexadecyltrimethylammonium bromide are completely dissolved.
[0047] In this invention, the molar ratio of sodium tungstate dihydrate to the mass ratio of hexadecyltrimethylammonium bromide is preferably 1 mmol:0.25 g to 1 mmol:1 g, and more preferably 1 mmol:0.05 g.
[0048] In this invention, the molar ratio of sodium tungstate dihydrate to bismuth nitrate pentahydrate is preferably 1:1.8 to 1:2.4, and more preferably 1:2.
[0049] In this invention, the temperature of the hydrothermal reaction is preferably 100-180°C, more preferably 120°C, and the time is preferably 12-48h, more preferably 24h.
[0050] In this invention, bismuth tungstate nanosheets are preferably dispersed in water to obtain a bismuth tungstate suspension; silver salt is dissolved in water, and the resulting silver salt aqueous solution is added dropwise to the bismuth tungstate suspension; an alkaline solution is added to adjust the pH value to 10-12; the resulting mixed solution is mixed with a reducing agent to carry out a reduction reaction to obtain a silver-bismuth tungstate catalyst.
[0051] In this invention, the mass-to-volume ratio of the bismuth tungstate nanosheets to water is preferably 1g:100mL to 1g:300mL, and more preferably 1g:200mL.
[0052] In this invention, the silver salt preferably includes silver nitrate, silver acetate, silver sulfate or silver chloride, and more preferably silver nitrate.
[0053] In this invention, the mass ratio of the silver salt to bismuth tungstate is 1:500 to 1:7000, more preferably 1:1000 to 7000, and even more preferably 1:1000.
[0054] In this invention, the concentration of the silver salt aqueous solution is preferably 0.05 to 1 mol / L, and more preferably 0.085 mol / L.
[0055] In this invention, the alkaline solution used to adjust the pH value preferably includes sodium hydroxide solution, sodium bicarbonate solution or ammonia water, and more preferably sodium hydroxide solution; the concentration of the alkaline solution is preferably 1 to 3 mol / L, and more preferably 1 mol / L.
[0056] In this invention, the reducing agent preferably includes ascorbic acid (C6H8O6) and sodium citrate dihydrate (Na3C6H5O7·2H2O), and the molar ratio of ascorbic acid to sodium citrate dihydrate is preferably 1:3 to 1:8, and more preferably 1:5.
[0057] In this invention, the mass ratio of the silver salt to the reducing agent is preferably 1:1 to 1:10, and more preferably 1:1.5 to 8.
[0058] In this invention, the temperature of the reduction reaction is preferably 80-120°C, more preferably 100°C, and the time is preferably 1-5 hours, more preferably 2 hours.
[0059] In this invention, the method of application preferably includes the following steps:
[0060] The photo-driven CO2 reduction to methanol was carried out in a 50 mL high-temperature and high-pressure reactor with a viewing window at the top for light transmission. The silver-bismuth tungstate catalyst was dispersed in water, loaded into the reactor and sealed. High-purity CO2 gas was introduced into the reactor to purge the air inside. This process was repeated three times, and the mixture was stirred for 30 min to allow the catalyst to reach CO2 gas adsorption saturation. The catalytic reaction was carried out under light irradiation and magnetic stirring to obtain methanol.
[0061] In this invention, the pressure of the CO2 gas is preferably 1 to 3 MPa, and more preferably 1 MPa.
[0062] In this invention, the light source for illumination preferably includes a xenon lamp, a mercury lamp, or an LED lamp, and is more preferably a xenon lamp, with a wavelength preferably between 350 and 780 nm.
[0063] In this invention, the temperature of the catalytic reaction is preferably 25-30°C, and the time is preferably 1-6 hours, more preferably 4 hours.
[0064] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0065] Example 1
[0066] 1 mmol Na2WO4·2H2O and 0.050 g CTAB were added sequentially to 60 mL of water and mixed to form a solution. 2 mmol Bi(NO3)35H2O was added under stirring and the mixture was stirred for 1 h. The suspension was poured into a 100 mL hydrothermal synthesis vessel and subjected to a hydrothermal reaction at 120 °C for 24 h. The mixture was then naturally cooled to room temperature in an oven. The catalyst was removed, washed with water several times, and dried to obtain bismuth tungstate nanosheets, denoted as BWO.
[0067] 0.2 g of bismuth tungstate nanosheets were dispersed in 40 mL of water to obtain a bismuth tungstate suspension. Silver nitrate was dissolved in water, and 21.8 μL of the resulting 0.085 mol / L silver nitrate aqueous solution was added dropwise to the bismuth tungstate suspension. 1 mol / L NaOH solution was added to adjust the pH to 11. Then, 6 mg of C6H8O6 and 50 mg of Na3C6H5O7·2H2O were added to carry out the reduction reaction. The reaction was heated in an oil bath at 100 °C for 2 h. After the reaction, the catalyst was washed multiple times with water and dried under vacuum at 60 °C for 12 h to obtain a silver-bismuth tungstate catalyst with a silver loading of 0.1% of the bismuth tungstate mass, denoted as 0.1%Ag / BWO-11.
[0068] In a 50mL high-temperature and high-pressure reactor with a transparent viewing window at the top, 0.05g of catalyst was dispersed in 20mL of water. Under sealed conditions, high-purity CO2 was introduced into the reactor to purge the air inside. This process was repeated three times. The pressure of CO2 gas was increased to 1MPa and the mixture was stirred for 30min to allow the catalyst to adsorb CO2 gas to reach saturation. The reaction was carried out at 25℃ for 4h under irradiation with a 300W xenon lamp with a wavelength of 350-780nm and magnetic stirring at 600r to obtain methanol.
[0069] Example 2
[0070] The only difference from Example 1 is:
[0071] Bismuth tungstate nanosheets, denoted as BWO, were prepared according to the method in Example 1.
[0072] In the preparation of silver-bismuth tungstate catalysts, the pH value was adjusted from 11 to 10, 10.5, 11.5 and 12 respectively, and silver-bismuth tungstate catalysts under different pH conditions were obtained, which were denoted as 0.1%Ag / BWO-10, 0.1%Ag / BWO-10.5, 0.1%Ag / BWO-11.5 and 0.1%Ag / BWO-12 respectively.
[0073] Other conditions were the same as in Example 1, and the silver-bismuth tungstate catalysts prepared under different pH conditions were used as catalysts to carry out photo-driven CO2 to sodium methoxide production.
[0074] Example 3
[0075] The only difference from Example 1 is:
[0076] Bismuth tungstate nanosheets, denoted as BWO, were prepared according to the method in Example 1.
[0077] In the preparation of silver-bismuth tungstate catalysts, the volume of silver nitrate aqueous solution added was changed from 21.8 μL to 65.4 μL and 152.6 μL, respectively, to obtain silver-bismuth tungstate catalysts with different Ag loadings, which were denoted as 0.3% Ag / BWO, 0.5% Ag / BWO, and 0.7% Ag / BWO, respectively.
[0078] Other conditions were the same as in Example 1, and the silver-bismuth tungstate catalysts prepared under different pH conditions were used as catalysts to carry out photo-driven CO2 to sodium methoxide production.
[0079] Characterization experiment
[0080] 1. X-ray diffraction was performed on bismuth tungstate and 0.1% Ag / BWO-11 prepared in Example 1, and 0.1% Ag / BWO-10, 0.1% Ag / BWO-10.5, 0.1% Ag / BWO-11.5, and 0.1% Ag / BWO-12 prepared in Example 2 using an X-ray diffractometer. The diffraction patterns were analyzed, and the results are shown below. Figure 1 ;
[0081] Figure 1 The XRD patterns of the silver-bismuth tungstate catalysts prepared under different pH conditions in Example 1 (bismuth tungstate), 0.1% Ag / BWO-11, and Example 2 are shown below. Figure 1 As shown, the diffraction peaks of the silver-bismuth tungstate catalyst prepared in Example 1 are all consistent with the structure of the bismuth tungstate standard card (PDF#73-2020), and no Ag diffraction peaks are observed. This is because the Ag loading is relatively small and it is uniformly distributed on the surface of the bismuth tungstate.
[0082] 2. The SEM spectra of bismuth tungstate and 0.1% Ag / BWO-11 prepared in Example 1 were obtained using scanning electron microscopy combined with energy-dispersive X-ray spectroscopy. The results are shown in [Figure 1]. Figure 2 ;
[0083] in Figure 2In the image, a is the SEM image of bismuth tungstate in Example 1, and b is the SEM image of 0.1% Ag / BWO-11 in Example 1. It can be seen that the silver-bismuth tungstate catalyst still exhibits a flower-like structure assembled from 2D nanosheets, indicating that the introduction of Ag and the change of pH have little effect on the morphology of the catalyst.
[0084] 3. N2 adsorption-desorption experiments were conducted on the bismuth tungstate and 0.1% Ag / BWO-11 prepared in Example 1, and the 0.1% Ag / BWO-10, 0.1% Ag / BWO-10.5, 0.1% Ag / BWO-11.5, and 0.1% Ag / BWO-12 prepared in Example 2. Data were obtained using a gas adsorption analyzer, and the specific surface area, pore volume, and pore size of each catalyst were calculated. The results are shown in Table 1 and [Table data would be inserted here]. Figure 3 , Figure 3 The N2 adsorption-desorption isotherm distribution (a) and pore size distribution (b) are for bismuth tungstate prepared in Example 1, 0.1% Ag / BWO-11, and silver-bismuth tungstate catalyst prepared in Example 2 under different pH conditions.
[0085] Depend on Figure 3 As can be seen from a, the N2 adsorption-desorption isotherms of bismuth tungstate and the silver-bismuth tungstate catalyst prepared in Example 1 both exhibit type IV isotherms and have type H3 hysteresis loops, indicating the formation of crack-like pores, which is consistent with their plate-like morphology; Figure 3 As shown in b, the pore size distribution curve confirms the existence of mesopores in the catalyst, which can provide high-speed transport channels, accelerate the mass transfer of reactants, and facilitate their participation in subsequent interfacial catalytic processes.
[0086] Table 1. Specific surface area, pore volume, and pore size of bismuth tungstate catalysts prepared in Example 1, 0.1% Ag / BWO-11, and Example 2 under different pH conditions.
[0087]
[0088]
[0089] As shown in Table 1, the specific surface area of the bismuth tungstate catalyst increased after silver loading. The larger specific surface area provides more active sites, which is beneficial to the reaction.
[0090] 4. (1) The light absorption properties of bismuth tungstate, 0.1% Ag / BWO-11 prepared in Example 1, and 0.1% Ag / BWO-10, 0.1% Ag / BWO-10.5, 0.1% Ag / BWO-11.5, and 0.1% Ag / BWO-12 prepared in Example 2 were studied using a UV-Vis diffuse reflectance spectrophotometer. Figure 4 a; Figure 4In Figure a, the UV-Vis DRS spectra of bismuth tungstate, 0.1% Ag / BWO-11, and silver-bismuth tungstate catalysts prepared under different pH conditions in Example 1 and Example 2 are shown.
[0091] like Figure 4 As shown in Figure a, compared to pure BWO, the Ag-loaded BWO catalyst exhibits enhanced light absorption in the visible light region, which is attributed to the LSPR effect of Ag. When light irradiates the surface of Ag nanoparticles, it drives the collective oscillation of electrons on the Ag surface. When the incident light frequency matches the oscillation frequency of Ag free electrons, resonance occurs, which enhances the collective oscillation of electrons. This is macroscopically manifested as a strong characteristic absorption peak in the ultraviolet-visible absorption spectrum.
[0092] (2) Figure 4 Figure b shows the Tauc curves of the silver-bismuth tungstate catalysts prepared in Example 1, 0.1% Ag / BWO-11, and Example 2 under different pH conditions; the band gap of the catalyst can be obtained according to the Tauc equation, such as... Figure 4 As shown in Figure b, the band gaps of BWO, 0.1%Ag / BWO-10, 0.1%Ag / BWO-10.5, 0.1%Ag / BWO-11, 0.1%Ag / BWO-11.5 and 0.1%Ag / BWO-12 are 2.73, 2.52, 2.54, 2.52, 2.23 and 2.37 eV, respectively. Compared with BWO, the band gaps of the Ag-supported catalysts are all narrower, which expands the photoresponse range of BWO, has good light absorption ability, and can also excite more electrons for CO2 activation.
[0093] (3) The temperature changes of bismuth tungstate catalysts prepared in Example 1, 0.1% Ag / BWO-11, and silver-bismuth tungstate catalysts prepared in Example 2 under different pH conditions were tested using an infrared thermal imager after irradiation with light from 350 to 780 nm. Bismuth tungstate and the silver-bismuth tungstate catalyst prepared in Example 1 were placed on glass plates and irradiated with light for 10 min. The temperature changes of the different catalysts were monitored, and the results are shown in […]. Figure 4 c;
[0094] Figure 4 Figure c shows the temperature change curves of the silver-bismuth tungstate catalysts prepared under different pH conditions in Example 1 (bismuth tungstate, 0.1% Ag / BWO-11) and Example 2 under light irradiation. Figure 4 As shown in Figure c, after 10 minutes of light irradiation, the catalyst temperature increased. The temperature of the Ag-loaded catalyst was higher than that of pure BWO. The increase in catalyst temperature indicates that it has photothermal conversion capability. The introduction of Ag can further enhance the photothermal effect generated on the catalyst surface, strengthen CO2 conversion, and thus promote photocatalytic CO2 reduction.
[0095] Performance testing
[0096] 1. The methanol content was determined using an Agilent 8890 gas chromatograph, and the methanol yield was calculated. The results are shown below. Figure 5 And Table 2.
[0097] Figure 5In the diagram, a shows the performance of the silver-bismuth tungstate catalysts prepared in Example 1 with bismuth tungstate, 0.1% Ag / BWO-11, and Example 3 under different Ag dosage conditions in the photocatalytic CO2 to methanol conversion. b shows the performance of the silver-bismuth tungstate catalysts prepared in Example 1 with bismuth tungstate, 0.1% Ag / BWO-11, and Example 2 under different pH conditions in the photocatalytic CO2 to methanol conversion. c shows the performance of the photothermal methanol conversion of the bismuth tungstate catalysts prepared in Example 1 with bismuth tungstate, 0.1% Ag / BWO-11, and existing BWO-based catalysts. QDh-BWO is derived from Jiang Z y, Liang X z, Zheng H l, et al. Photocatalytic reduction of CO2 tomethanol by three-dimensional hollow structures of Bi2WO6 quantum dots[J]. Applied Catalysis B:Environmental,2017,219:209-215; single-unit-cell BWO is derived from Liang L, Lei F, Gao S, et al. Single Unit Cell Bismuth Tungstate LayersRealizing Robust Solar CO2 Reduction to Methanol[J].Angewandte Chemie-International Edition, 2015,54(47):13971-13974; BWO comes from Li H, Zhang J c, Yu J g, et al. Ultra-thin carbon-doped Bi2WO6 nanosheets for enhanced photocatalyticCO2 reduction[J]. Transactions of Tianjin University, 2021, 27(4): 338-347; BWO-OV2 comes from Fan HX, Liu T, Zhen LF, et al. Evaluating the role of oxygen vacanciesin CO2 photothermal catalytic reduction to methanol over 2D Bi2WO6[J].ScienceChina Materials, 2025, 68(2): 464-471; MoS2 / BWO comes from Dai W, Yu J, Deng Y, et al.Facile synthesis of MoS2 / Bi2WO6 nanocomposites for enhanced CO2 photoreduction activity under visible light irradiation[J]. Applied Surface Science, 2017, 403: 230-239; Table 2 shows the methanol yields in Example 1 for photothermal methanol production using bismuth tungstate, 0.1% Ag / BWO-11, and existing BWO-based catalysts.
[0098] Table 2 shows the methanol yields during photothermal methanol production using bismuth tungstate, 0.1% Ag / BWO-11, and existing BWO-based catalysts in Example 1.
[0099]
[0100] analyze Figure 5 a, Figure 5 b and Figure 5 According to Table 2, the catalyst prepared with an Ag loading of 0.1% and a pH of 11 exhibits the best reaction performance and the highest methanol yield.
[0101] 2. (1) Calculate the methanol yield, carbon dioxide adsorption amount and proportion of moderately alkaline sites of bismuth tungstate and 0.1% Ag / BWO-11. The results are shown in Table 3.
[0102] Table 3 CO2 adsorption capacity of BWO and 0.1% Ag / BWO-11
[0103]
[0104] Table 3 shows the CO2 adsorption capacity of BWO and 0.1% Ag / BWO-11 catalyst, which are 2.33 and 2.55 mmol / g, respectively. The introduction of Ag increased the CO2 adsorption capacity of BWO, and the increase in basic sites is beneficial to CO2 adsorption, which in turn is beneficial to the increase in methanol yield, confirming that Ag improves the adsorption and activation of CO2.
[0105] (2) Figure 6 The CO2-TPD chromatogram for bismuth tungstate and 0.1% Ag / BWO-11 in Example 1 is shown below. Figure 6As shown, the CO2 desorption signal of 0.1% Ag / BWO-11 shifts towards higher temperatures, indicating that Ag loading enhances the interaction between BWO and CO2, which is beneficial for CO2 activation and reduction. Increasing the number of surface basic sites is beneficial for CO2 adsorption and activation. Moderately basic sites not only allow electrons to flow between CO2 and the catalyst, but also have chemical bonds of appropriate strength that facilitate CO2 participation in subsequent reactions. The increased number of strong basic sites in 0.1% Ag / BWO-11 further enhances CO2 adsorption.
[0106] 3. Figure 7 Figure a shows the performance evaluation of 0.1% Ag / BWO-11 prepared in Example 1 within 4 hours under different conditions (no light at 25°C; temperature rise from 25°C to 48.9°C within 4 hours without light; and light at 25°C). Figure 7 Figure b shows the performance evaluation of 0.1% Ag / BWO-11 prepared in Example 1 at 4 hours under different conditions (no light at 25°C; temperature rise from 25°C to 48.9°C within 4 hours without light; light at 25°C); combined with... Figure 7 a and Figure 7 As shown in b, after the introduction of light, the methanol yield under the light condition is 3.94 times and 2.20 times that of the other two conditions, respectively. The yield under the light condition is significantly better than the methanol yield under the conditions without light and under the conditions without light but with external heating. This indicates that the photothermal synergistic effect of the present invention increases the activity of CO2 to methanol conversion.
[0107] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. Use of a silver-bismuth tungstate catalyst in the photocatalytic production of methanol from CO2, characterized in that, The application relates to a method for preparing a silver-bismuth tungstate catalyst. The method comprises the following steps: The silver-bismuth tungstate catalyst is dispersed in water, CO2 gas is introduced under airtight conditions, and a catalytic reaction is carried out under light irradiation to obtain methanol; The initial temperature of the catalytic reaction is 25-30 DEG C; The size of silver particles in the silver-bismuth tungstate catalyst is 20-50 nm; The loading amount of silver in the silver-bismuth tungstate catalyst is 0.1-0.7% of the mass of bismuth tungstate; The preparation method of the silver-bismuth tungstate catalyst comprises the following steps:
2. Use according to claim 1, characterized in that, The bismuth tungstate nanosheet, silver salt and water are mixed, the pH value is adjusted to 10-12, the obtained mixed solution is mixed with a reducing agent, and a reduction reaction is carried out to obtain the silver-bismuth tungstate catalyst. The preparation method of the bismuth tungstate nanosheet comprises the following steps:
3. Use according to claim 2, characterized in that, The sodium tungstate dihydrate, cetyltrimethylammonium bromide, bismuth nitrate pentahydrate and water are mixed, and a hydrothermal reaction is carried out to obtain the bismuth tungstate nanosheet.
4. Use according to claim 3, characterized in that, The molar amount of the sodium tungstate dihydrate and the mass of the cetyltrimethylammonium bromide are in a ratio of 1 mmol:0.25 g-1 mmol:1 g, and the molar ratio of the sodium tungstate dihydrate and the bismuth nitrate pentahydrate is 1:1.8-1:2.
4.
5. The use according to claim 1, characterized in that, The temperature of the hydrothermal reaction is 100-180 DEG C, and the time is 12-48 h.
6. Use according to claim 1, characterized in that, The silver salt comprises silver nitrate, silver acetate, silver sulfate or silver chloride, and the mass ratio of the silver salt and bismuth tungstate is 1:500-1:7000.
7. The use according to claim 1, characterized in that, The alkali solution used for adjusting the pH value comprises a sodium hydroxide solution, a sodium bicarbonate solution or ammonia water, and the concentration of the alkali solution is 1-3 mol / L.
8. The use according to claim 1, characterized in that, The reducing agent comprises ascorbic acid and sodium citrate dihydrate, the molar ratio of the ascorbic acid and sodium citrate dihydrate is 1:3-1:8, and the molar ratio of the silver salt and reducing agent is 1:1-1:
10.
9. The use according to claim 1, characterized in that, The temperature of the reduction reaction is 80-120 DEG C, and the time is 1-5 h.
10. The use according to claim 1, characterized in that, The pressure of the CO2 gas is 1-3 MPa. The light source of the light irradiation comprises a xenon lamp, a mercury lamp or an LED lamp, and the wavelength is 350-780 nm; The time of the catalytic reaction is 1-6 h.
Citation Information
Cited By
Ag-Bi2WO6 heterojunction photocatalyst as well as preparation method and application thereof
CN121797311A
Cu2O-Bi vacancy Bi2WO6 heterojunction photocatalyst as well as preparation method and application thereof
CN121892159A